PENGARUH HARGA, PENANGANAN KOMPLAIN, DAN BRAND IMAGE TERHADAP KEPUTUSAN PENGGUNAAN JASA PENGIRIMAN PAKET PADA PT POS INDONESIA (PERSERO) KANTOR CABANG TEBING TINGGI - Rahmadana, Risky; Mardhiyah, Ainun (Transpublika Publisher, 2023)
This study was conducted with the aim of analyzing the impact of certain variables, namely price, complaint handling, and brand image, on decisions to use package delivery services within PT Pos Indonesia (Persero) Tebing Tinggi Branch Office. This research adopts a quantitative approach with associative research methods to understand the relationship between these variables. Sampling was carried out using purposive sampling technique, where 90 respondents were selected as samples representing the research population. Through data analysis, the results showed that price, complaint handling, and brand image have a significant influence both partially and simultaneously on the decision to use package delivery services at PT Pos Indonesia (Persero) Tebing Tinggi Branch Office. Thus, these findings illustrate that the variables of price, complaint handling, and brand image together have an important role in shaping decisions to use package delivery services. The results of this study can help PT Pos Indonesia (Persero) Tebing Tinggi Branch Office in improving marketing strategies, especially in setting prices, improving complaint handling, and strengthening brand image. This aims to increase user choice of the company's package delivery services.